PENERAPAN METODE EXPERIENTAL LEARNING DALAM MENINGKATKAN KETERAMPILAN MENULIS KARANGAN NARASI SISWA KELAS IV SDN KIP BARA-BARAYA 1 - Ulfa Khairunnisa; Aliem Bahri, Abdan Syaku (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the application of the Experiential Learning method in improving narrative writing skills in fourth grade students of SDN Kip Bara-Baraya 1. The problem raised in this study is the low ability of students to write interesting narrative essays. The method used in this study is Classroom Action Research (CAR) which is carried out in two cycles. Each cycle consists of planning, implementation, observation, and reflection. Data collection techniques are carried out through observation, narrative writing tests, and documentation. This approach is carried out in 2 cycles. The results of the study show that there is an increase in students' narrative writing skills as seen from the evaluation tests of cycle I and cycle II. The results of the evaluation test of cycle 1 with a percentage of 69% and increased in cycle II with a percentage of making essays of 89.04%. Based on the evaluation results, it can be concluded that the application of the Experiential Learning method which emphasizes direct experience, reflection, and real application can improve the narrative writing skills of fourth grade students of SDN Kip Bara-Baraya 1.